Coexistence of COVID-19 and acute ischemic stroke report of four cases - TUNÇ, Abdulkadir; ÜNLÜBAŞ, Yonca; ALEMDAR, Murat; AKYÜZ, Enes (Journal of clinical neuroscience, 2020)
•COVID-19 has neuro-invasion potential independently of the critical disease process.•Cerebrovascular diseases such as ischemia may develop in the course of disease.•Increased inflammation may be predicted by CRP and D-dimer levels.•The elder Covid-19 patients with prothrombotic risk factors should also be considered for the signs of stroke. Coronaviruses are revealed to target the human respiratory system mainly. However, they also have neuro-invasive abilities and might spread from the respiratory system to the central nervous system. Herein, we report four patients with COVID-19 simultaneously diagnosed with acute ischemic stroke. There were four stroke cases with simultaneously diagnosis of Covid-19 till the April 14, 2020 in the city of Sakarya, Turkey. They were aged between 45 and 77 years. All four cases were likely to have contracted the virus in Sakarya. The patients had all commonly reported symptoms of Covid-19. Three patients have elevated D-dimer levels, and two of them had high C-reactive protein (CRP) levels. They were managed symptomatically for both the infection and the stroke. Our findings suggest that ischemic cerebrovascular diseases may simultaneously develop in the course of Covid-19 independently of the critical disease process. Increased inflammation predicted by CRP and D-dimer levels may play a role in the formation of ischemia. In particular, elder patients with prothrombotic risk factors should also be considered for the signs of cerebrovascular events in addition to infectious symptoms.